Linguística de corpus e estilo: análises multidimensional e canônica na ficção de Machado de Assis - Kauffmann, Carlos Henrique (2020)
The goal of this study is to analyze linguistic variation across fictional prose of Brazilian writer Machado de Assis from the perspective of style, grounded theoretically and methodologically by Corpus Linguistics (Berber Sardinha, 2004) in order to highlight the author's main communicative and thematic aesthetic dimensions. To carry out this purpose, two corpora were collected: Machado de Assis's Literary Corpus (CLIMA), which comprises 9 novels and 76 short stories written by him (859,521 words), and Comparable Literary Corpus (CLIC), reference corpus constituted of 92 works by 23 writers from 1850-1910 period (3,386,037 words). Both were tagged for part-of-speech features and had their counting normalized to 1,000 words. A list of the most frequent words and lemmas from Corpus CLIMA was also compiled. Several multidimensional analyses (MDAs) were then performed to extract co-ocurrent groups of linguistic features or words and lemmas from textual variation, the so-called dimensions of functional or lexical variation (Biber, 1988; Berber Sardinha & Veirano Pinto, 2014, 2019). Standardized scores of the dimensions were individualized by text, enabling comparative and contrasting stylistic analyses. Two additive MDAs are initially presented, which compare the work of Machado de Assis with that of writers of the period and in relation to the functional dimensions of current Brazilian Portuguese (Berber Sardinha, Kauffmann & Acunzo, 2014a). Next, three complete MDAs were performed, two of which in the functional approach, to verify linguistic variation across the reference corpus and within the individual work of Machado de Assis, and one lexical MDA of the CLIMA corpus focused in identifying its main lexical dimensions. Additionally, a canonical correlation analysis was carried out to verify associations between the functional and lexical dimensions identified in Machado de Assis's work, leading to the emergence of three aesthetic dimensions, named "Formal introspective romanticism", "Sentimental oralized narrative", and "Dramatic representation"